2017
DOI: 10.5603/gp.a2017.0088
|View full text |Cite
|
Sign up to set email alerts
|

Screening for trisomy 21 based on maternal age, nuchal translucency measurement, first trimester biochemistry and quantitative and qualitative assessment of the flow in the DV — the assessment of efficacy

Abstract: Objectives: The aim of the study was to compare effects of addition of two methods of ductus venosus (DV) flow assessment: qualitative -the assessment of shape of the A-wave (positive or negative), and quantitative -based on the pulsatility index for veins (DVPI) to the basic screening for trisomy 21 at 11 to 13 + 6 weeks of pregnancy. Material and methods:The ultrasound examination was performed in 8230 fetuses in singleton pregnancies at 11--13 + 6 wks, as a part of a routine screening for chromosomal defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(30 reference statements)
2
2
0
Order By: Relevance
“…Our median maternal age was 31 years, which was comparable to other values registered in Spain (32.4 years in 2016) [23], Romania (29.6 years in 2017) [18,24] or in Poland (34 years in 2017) [19], for first-trimester screening population.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our median maternal age was 31 years, which was comparable to other values registered in Spain (32.4 years in 2016) [23], Romania (29.6 years in 2017) [18,24] or in Poland (34 years in 2017) [19], for first-trimester screening population.…”
Section: Discussionsupporting
confidence: 67%
“…Two other recent studies also reported similar detection rates [18,19] of 91.6% and 93.75%, respectively.…”
Section: Discussionsupporting
confidence: 56%
“…27,28 The use of the quantitative DV flow (DV PIV) for screening trisomy 21 has been shown in recent literature to provide more accurate results compared to the qualitative flow assessment with a low positive predictive value. 6,16,29 By using the ROC curve, our study shows that abnormal DV blood flow was present in 61.5% fetuses with chromosomal abnormalities with 63.6% sensitivity, and specificity of 60.3%. A study by Bilardo et al found an abnormal DV PIV or an abnormal "a wave" in the DV waveform sensitivity of 65% for detecting chromosomal abnormalities.…”
Section: Discussionmentioning
confidence: 87%
“…4 Accumulating evidence indicates that the DV flow profile is the main cardiovascular imaging marker influencing prenatal risk stratification in terms of adverse pregnancy outcomes that would include chromosomal abnormalities and cardiac anomalies. 5,6 The DV connects the umbilical vein to the inferior vena cava, providing highly oxygenated blood for fetal circulation. 7 A Doppler examination of the DV is typically performed quantitatively for assessing parameters, such as the DV pulsatility index (DVPI; the most frequent measure), DV resistive index (DVRI), time-averaged maximum velocity (TAMAX), and the ventricular systole/atrial contraction ratio (S/A ratio), or qualitatively focusing on the a-wave.…”
mentioning
confidence: 99%